INFLUÊNCIA DOS SUPORTES PSICOSSOCIAL E MATERIAL NO IMPACTO DO TREINAMENTO NO TRABALHO - CALIL, PRISCILA SOARES (2020)
This research has as general objective to test the model of prediction of the variables of the support to the transfer of training: (1) psychosocial support of the peers (colleagues), (2) psychosocial support of the supervisors and (3) material support on the training impact in the extensive work, considering the importance of human relationships in the face of material conditions and the lack of consensus identified in the literature. Its specific objectives were to carry out a systematic review of national and foreign literature on support for transfer of training and on the impact of training at work; identify which is the main predictor of the impact of training at work in breadth; investigate which type of support for training transfer has the greatest influence on the impact of training at work and verify whether the proposed model works differently for different groups: leaders and followers. Data collection was carried out for convenience, through the application of an online questionnaire. The responses to the scales of support to the transfer of training and the impact of training at work in amplitude and to the sociodemographic data of the 146 valid respondents were subjected to descriptive statistical analyzes, Cronbach's alpha, Kolmogorov-Smirnov normality test, Spearman correlations, regression analysis, analysis of variance and Mann Whitney test. The results revealed that the support for training transfer (psychosocial and material) predicts the impact of training at work in breadth, that the dimensions of support for training transfer, both when evaluated in a bifactorial way (material and psychosocial support) and when separated in psychosocial support from peers and supervisors, in addition to material support, positively influence the impact of training at work. Material and psychosocial support explained 33.3% and material, psychosocial support from peers and supervisors, 32.9%, respectively. The psychosocial support of peers was the main predictor of the impact of training at work in breadth. These results suggest that more proximal factors, such as peer support, can overcome the effect of more distal factors in promoting transfer and autonomy at work, that psychosocial support (peers and supervisors) has a greater influence on the impact of training at work in amplitude than the material support. Although the literature presents results that point out differences between the perceptions of leaders and followers, this study did not corroborate these results; the perception of psychosocial support of individuals with a leadership role does not differ from the perception of subordinate individuals. Here, a research opportunity is established, to outline the specific aspects (informational, instrumental, emotional and performance, in addition to the trainee, training and environment characteristics) of the supervisory support and then leaders, who have the most consistent relationship with the training transfer. The results of this research reinforce that the perceived support is essential for the training impact, mainly the support of peers, which is perhaps due to the direct contact established between co-workers with the same functional status and the continuous flow of information. The highlight of the challenges in this research area is mainly related to the learning process and to the methodological improvement of research.